A simple and rapid colorimetric detection of methanol, ethanol, and isopropanol and its application toward alcohol-based hand sanitizer quality control - Warongrit Sukma; Cheerapa Boonyakong; Thitiphan Chaiphet; Supakarn Chamni (Green Chemistry Letters and Reviews)
A practical colorimetric analysis for alcohol determination was devised using a composite of food colorants, specifically a green solution of brilliant blue FCF and tartrazine at a ratio of 1:5 v/v. This colorimetric method was characterized by its simplicity, user-friendliness, environmental compatibility, cost-effectiveness, and suitability for self-measurement through visual examination. The colorimetric procedure entails admixture 1 mL of the alcohol sample with 50 µL of the green test solution and 250 µL of a 30% NaOH solution at ambient temperature. The ensuing color changes were visually assessed within 5 min. Through color sensing, methanol, ethanol, and isopropanol were identified by the manifestation of lemon yellow, orange, and biphasic solutions, respectively. Ethanol was semi-quantified based on color sensing from green to orange, with corresponding concentration ranges. The limit of detection for both methanol and ethanol was determined to be 30% v/v. The developed method demonstrated an accuracy of 93%, with the error range of 1 − 10% v/v and standard deviation of 3.9% v/v, as confirmed by the analysis of 100 commercially available alcohol-based hand sanitizers. This methodology has the potential for further expansion to encompass a wide range of rapid colorimetric analyses of products containing alcohol, including food items, alcohol raw materials, and cosmetics.